2022
DOI: 10.1186/s12889-022-13132-w
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between perceived risk and actual risky sexual behaviors among undergraduate university students in mainland China: a cross-sectional study

Abstract: Background HIV prevention, diagnosis, treatment and care services might be hampered by inaccurate risk assessment. This study aimed to investigate the extent of and factors associated with the discordance between perceived risk and actual risky sexual behaviors among undergraduates in mainland China, guided by the Anderson's behavioral model. Methods This study involved a secondary analysis of cross-sectional data collected during the fall semester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…This study also indicated male college students with heightened HIV risk perceptions were more likely to engage in condomless sex. A few studies have stressed the threating existence of risk discordance recently, meaning people who perceived low risk actually participated into high risk behaviours (49,50). However, compared to that, the phenomena in our study was even detrimental and complicated.…”
Section: Discussioncontrasting
confidence: 51%
“…This study also indicated male college students with heightened HIV risk perceptions were more likely to engage in condomless sex. A few studies have stressed the threating existence of risk discordance recently, meaning people who perceived low risk actually participated into high risk behaviours (49,50). However, compared to that, the phenomena in our study was even detrimental and complicated.…”
Section: Discussioncontrasting
confidence: 51%
“…Recent studies have shown that groups with different health beliefs produce different health behaviors, and groups with the same health beliefs also have different health behaviors, which may be due to differences in individuals’ behavioral tendencies [ 61 , 62 ]. Knowledge-Attitude/Belief-Practice(KAP) theory suggests that human behavior is related to cognition, values, and beliefs and that establishing health beliefs is a critical component in promoting physical exercise behavior [ 63 ]. The central aspect of college sports work is cultivating students’ sports literacy and lifelong consciousness of sports.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proportion of the commercial sex behavior group that insisted on using condoms each time during sex was only 26.8%. Studies have shown that the lack of conver-sion from knowledge to preventive measures in condom use among male college students is serious, and complex unsafe sexual behaviors increase the difficulty of intervention [33][34][35]. Therefore, to educate college students on HIV/ AIDS prevention, it is necessary to emphasize that the individual is the first person responsible for their own health.…”
Section: Discussionmentioning
confidence: 99%